Development Of E-LKPD Assisted Liveworksheet On Opportunity Material - Ariska, Rita; Andinasari, Andinasari; Sistyawati, Risda Intan (Prima: Jurnal Pendidikan Matematika, 2025)
This research aims to make E-LKPD assisted by liveworksheet on chance material for vocational students, to determine the validity and practicality as well as potential effects. This research uses the AADIE development model. The stages of ADDIE development are as follows: (1) analysis stage, (2) design stage, (3) development stage, (4) implementation stage, and (5) assessment stage. The validation results showed 91.67% from media experts with the category "very valid" and 88.33 from material experts with the category "very valid". The practicality test at the small group stage obtained 91.94% with the category "very practical, and the field test showed a potential effect on learning motivation of 92.07% with the category "very high".